Sustainable consumption, resonance, and care - Wahlen, Stefan; Stroude, Aurianne (Frontiers in Sustainability, 2023)
Consumption is a key issue for more sustainable development. In our quest to understand the role of care for more sustainable consumption we make use of the concept of resonance. Resonance assists in explaining the role of care for more sustainable consumption, emphasising the relationships people have with the world. Through resonance we add to debates on sustainable consumption that focus on the good life. Resonance describes a responsive mode of being in the world and therefore depends on how we (passively) experience the world and how we (actively) appropriate or assimilate it. It is a reciprocal relationship between the individual and the world through which both are shaped. According to Hartmut Rosa, resonance as world relationship can be detected on three axes on which individuals relate to the world: 1) horizontal (people and politics), 2) diagonal (things), 3) vertical (collective singulars such as nature, art, history, religion). Using these axes as heuristic, we analyse solicited journaling method as well as in-depth interview data. Caring relationships can be detected along the three axes of resonance. Resonance thus helps to advance the characteristics of care as not limited to relationships between humans but also for things or collective singulars such as nature. Resonance also highlights how caring relationships support sustainable consumption in a positive way through focusing on its relational and reciprocal dimensions.